Peran conscientiousness personality trait dan iklim sekolah dalam pencegahan perundungan - Rahmawati, Sri W. (Konsorsium Psikologi Ilmiah Nusantara, 2018)
The aim of this study was to examine the role of conscientiousness personaity trait and school climate toward bullying. A sample of 616 senior high school students from five regions in Jakarta were acquired for this study using cluster random sampling technique. The NEO PI-R Scale, The School Climate Scale, and The Scale of Bullying were used in this study. The research hypothesized that there would be a significant negative correlation between the personality trait and school goals and norms on bullying. The study found that conscientiousness personality trait and school goals and norms in school settings have significant negative correlations to bullying. Regression test results indicated that conscientiousness trait and school goals and norms contributed 4.2% and 3.8% on bullying. It was concluded that to obtain the optimal results, bullying prevention programs in schools should consider improving students’ personality trait and the school climate.